The Mastery of The Teochew Dialect and Mandarin Chinese of Chinese Youths - Tjen Veronica; Lily Thamrin; Lusi Lusi; Suhardi Suhardi (STKIP Singkawang, 2023)
This research aimed to determine the mastery of Teochew and Mandarin Chinese among Chinese youths in Pontianak. This research employed a descriptive method with questionnaires as data collection tools. The research participants were students from four senior high and vocational high schools in Pontianak. In learning a language, it is necessary to master four language skills. They are listening, speaking, reading, and writing skills. In terms of listening skills, respondents with the highest percentage (39%) were the respondents who understood the Teochew dialect fluently, and the highest (54%) were respondents who understood Mandarin Chinese little fluently (54%). In speaking skills, respondents with the highest percentage (32%) were respondents who spoke the Teochew dialect fluently, and the highest (54%) were respondents who spoke Mandarin Chinese little fluently. In reading skills, respondents with the highest percentage (27%) were those who read the Teochew dialect fluently, and the highest (46%) were respondents who were a little fluent in Mandarin Chinese. In writing skills, respondents with the highest percentage (25%) were those who wrote the Teochew dialect quite fluently, and the highest (50%) were respondents who were a little fluent in writing Mandarin Chinese. From the research, the researcher concluded that overall, the Chinese youths were more proficient in the Teochew dialect than Mandarin Chinese.